Public Relations Management Performance Measurement: Designing Key Performance Indicator Case Study In Hospital X - Palupi, Maria Diah (Global and Policy Journal of International Relations, 2019)
ABSTRACTIn attempt of hospital development, hospital X focus on current performance measurement only on marketing performance in terms of sales volume and sales revenue for maximizing profits. Performance evaluation of public relations activities at hospital X so far have not had the performance measurement. As the result; the contribution of public relations, in order to support the activities of the organization, are not measurable. This study aims to measure the performance of PR management by designing key performance indicators by conducting a process of identifying stakeholder necessity exists in hospital X. The identification of stakeholder necessity exist in hospital X will then become the basis of designing PR’s KPI. The stakeholder in this study are director, head of marketing, staff as internal stakeholder and customer, supplier and regulator as external stakeholder. The results of this study is the assessment of PR performance which include work result assesment formulated six responsibilities namely, customer satisfaction, customer complaints, fostering community, events, social media content and website traffic. While the work behavior assesment with the indicators of competence namely communicative, flexibility, discipline, teamwork, customer service.Keywords: Public relations, stakeholder management, performance assessment, key performance indicator DOI : https://doi.org/10.33005/jgp.v7i02.1833